Die Lebenszeugnisse Oswalds von Wolkenstein, Band 4 - Schwob, Ute Monika; Schwob, Anton (2011)
The Tyrolean knight Oswald von Wolkenstein (ca 1376 - 1445) is considered to be the most important German poet and composer of the Late Middle Ages. Besides his songs and compositions more than 1000 documents bear evidence of his chivalrous career and the medieval life of the lower nobility in all its social, economic and legal details. This exceptional historical attestation came down to us in ca 40 archives spread all over Austria, Italy, Germany and neighbouring countries. Partly known and with exceptions not published before this five volume edition presents the material in a totally new edition following the rules of historic-diplomatic editions, based on new transcriptions and accompanied by source descriptions as well as ample commentaries. Volume IV comprises the years 1438 to 1442, a period that shows how Wolkenstein is establishing himself as a leading member oft Tyrolean nobility, renown as legal adviser as well as a land-owner involved in arguments. Der Tiroler Adelige Oswald von Wolkenstein (um 1376 - 1445) gilt als einzigartiger Exponent der spätmittelalterlichen deutschen Lyrik. Neben seinem literarisch-musikalischen Werk hat er der Nachwelt noch eine historische Überlieferung hinterlassen, die Beachtung verdient. Sie soll in einem fünfbändigen Werk, dessen 4. Band hier vorgelegt wird, ediert und kommentiert werden. Aus Briefen, Urkunden und Akten lassen sich ebenso eine individuelle ritterliche Karriere wie das standestypische Leben des mittelalterlichen Herrenstandes mit seinen sozialen Vernetzungen, ökonomischen Grundlagen und rechtlichen Möglichkeiten ablesen. Die Texte wurden in rund 40 in- und ausländischen Archiven ausgehoben, von Grund auf neu transkribiert, beschrieben, nach einheitlichen Editionsprinzipien bearbeitet und von detaillierten Kommentaren begleitet. Band 4 umfasst die Zeit von 1438 bis 1442 und zeigt den Wolkensteiner vor allem als streitbaren Grundherrn, als Rechtssachverständigen und zunehmend als bedeutenden Politiker in der Grafschaft Tirol.